Analisis Efektivitas Pelayanan Booking Service Online Honda AHASS: Studi Kasus pada Pengguna Honda di Lingkungan Mahasiswa Universitas Bumigora - Mulawarman, Logi; Jatmiko Jati, Lalu; Anggriani, Rini; Umiyatun, Reni (Rifa'Institute, 2023)
Some Honda AHASS motorcycle repair shops still faces bad system that give impact on overload customers when registration for service at the repair shop. However, most of the repair shops currently have switched and taken advantage of technological developments to deal with the above problems by providing online booking service program. This program was created to make it easy for Honda customers or users to register their bike to get service program. This study aims to explore depthly the effectiveness of the Honda AHASS online booking service among university students. This research is a qualitative research with a case study approach. Data collection was carried out by interviewing 25 Bumigora University students. There are two findings in this study. First, online booking service program easy to use for students because they are able to save time in ordering bike service program. 15 out of 25 students said it was easy to use this program. Second, this program gets a positive response from students and this shows that there is satisfaction from students with the online booking service. the application of online booking service services still needs to be maximized because there are still some students who do not know about the existence of this service.